Towards a New Christian Sexual Ethics in the Light of Hiv/Aids - Zimmermann, Armin (International review of mission, 2004)
According to various statistics, about 90% of the HIV infections in Africa, south of the Sahara are got through unprotected sexual intercourse. This clearly suggests that the key to a reduction of the HIV infection rate is a change in our sexual behaviour. In this article, therefore, I want to propose some guidelines “Towards a New Christian Sexual Ethics in the Light of HIV/AIDS”, and take into consideration various aspects of an African context. Next to upholding the positive value of our sexuality as part of God's good creation, we have to empower women to determine for themselves if, when, how and with whom they want to have sexual contact. We have to emphasise values like intimacy, love, commitment and responsibility, and we should discourage casual sex and prostitution. We may also have to reconsider the relationship between sexual relationships and activities and marriage. While confirming marriage as the ideal context of sexual relationships and activities, we may encourage people to practice their sexuality only within long-term permanent relationships that should be characterised by the principles stated above. However, since we know that humans are not perfect, we have to reckon with people who are either unwilling or unable to follow the proposed guidelines, and at this point we, as churches and Christians, cannot avoid the discussion about condoms. According to my point of view, there is no alternative than to advise those unwilling or unable people always to consistently and correctly use condoms, while at the same tune we should encourage them to change their behaviour. One of the greatest problems to introducing the proposed guidelines is certainly the widespread difficulty there is to talk about sexual matters. This is something that we have to overcome in order to save people from dying, and to lead them into real loving relationships.